Digital and traditional communication with kin: displacement or reinforcement? - Danielsbacka Mirkka; Tammisalo Kristiina; Tanskanen Antti O (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
A salient question in the digital era is whether new forms of digital communication (e.g. instant messages, video calls, e-mails) have displaced or reinforced more traditional forms of communication (e.g. meeting face-to-face, contact by phone, sending letters/postcards). These opposing hypotheses, i.e. digital communication as a reinforcer versus a displacer, have attracted abundant attention among scholars; however, studies have scarcely explored these hypotheses in the context of communication among kin. Using large-scale and population-based data of 1,945 young to middle-aged (18-55 year-olds) and 2,663 older (68-73 year-olds) Finns, we tested the predictions derived from the displacement and reinforcement hypotheses in several kin dyads (parent-child, grandparent-grandchild, siblings, and aunt/uncle-niece/nephew). The results supported the reinforcement hypothesis in all kin dyads, and in both younger and older adults. Associations between digital and traditional communication were positive even after controlling for a wide range of potentially confounding factors. Hence, it can be concluded that digital means reinforce rather than displace traditional forms of contact.